Estimativa de Recursos de Carvão Utilizando Métodos Geoestatísticos - DA SILVA, JORGE LUIS BARBOSA; ZOUAIN, RICARDO NORBERTO AYUP (Pesquisas em Geociências, 2001)
This paper presents a geostatical method for resources estimation of a coal seam. The coal seam is refered to as “I” and belongs to Leão-Butiá coal deposit, located at central east region of Rio Grande do Sul State, southernmost Brazil. data set are composed by 182 measures of coal seam thickness obtained by drill holes. To evaluate seam thickness, initially in this work, was approached the basic descriptive statistic about the sampled data set. To continue, spatial continuity analysis was performed and to conclude was carried out an ordinary kriging estimation process. Considering the tree previous process was accomplished a block kriging that allowed estimate mean and variance of seam thickness and extension of sampled total area. With this data it was possible to calculate the coal seam volume. Knowing coal local density and multiplying it by the volume determines coal seam quantities (ton) for which a confidence interval was estimated. To compare estimate and true values a cross validation was made, using the model of kriging and the sampled data set. A histogram is presented to show the average error for the model that should be null to confirm the process.